SISTEM SCADA UNTUK MEMANTAU LEVEL AIR BERBASIS LABVIEW - , INGGIT PALUPI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
SCADA system has been designed to facilitating and monitoring the water level based on labview. This system consists of a distance sensor SRF04, control circuit valve, relay circuits, Arduino systems and system software labview. Control valve and the water level will be displayed on a laptop thru labview. The design of the control valve and water level monitoring use SRF04 distance sensor, Arduino, communications and software programs. Software program use labview 2013. Control and monitoring system can be implemented using Arduino and labview on laptop. SRF04 sensors are placed on a bucket lid is used to know the distance of the water to bucket. Data from the sensors will go on the Arduino which then will be monitored and controlled. Control of the water level will activate or to disable the appropriate conditions are met actuators. So that the water level in the bucket can be maintained. Actuator control is 24 Volt valve.